A method for preparing high-performance battery materials regulated by generalized fluorine
By adopting a monomer fluorine-containing strategy in lithium metal battery materials and a solvent without fluorine-containing strategy, combined with strict assembly and baking processes, the existing battery materials are not resistant to high voltage and poor cycle stability, and the preparation of high-performance battery materials is achieved, with excellent high voltage resistance and stability performance.
Patent Information
- Application Number
- CN202411979103.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-31
- Publication Date
- 2025-04-08
AI Technical Summary
The existing in-situ cured semi-solid polymer electrolytes are not resistant to high voltage and have poor cycle stability, and cannot achieve high energy density, high specific energy, high mechanical strength and high interface stability at the same time.
The lithium metal battery material is prepared by using a strategy of monomer fluorine-containing and solvent-free fluorine-containing strategy. By controlling the proportion of lithium salts, vinyl carbonate, monomers, crosslinking agents and initiators, combined with strict mixing sequence and baking conditions, a high-performance battery material with generalized fluorine regulation is formed.
It significantly improves the high-voltage resistance and stability of the battery material, enhances the ionic conductivity and mechanical properties of the electrolyte, and extends the cycle life of the battery.
Smart Images

Figure CN119786749A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the field of lithium battery material preparation, and in particular relates to a method for preparing a generalized fluorine-regulated high-performance battery material. Background Art
[0003] Solid polymer electrolytes have the characteristics of high flexibility and good electrode interface compatibility, which can effectively solve the problems of inorganic ceramic electrolytes that are difficult to commercialize due to high brittleness, difficult processing, and poor interface compatibility. There are many methods for preparing polymer electrolytes. Compared with many other methods, the in-situ polymerization method has the advantages of simple process and convenient production. However, in many existing studies, the polymer electrolytes prepared by in-situ polymerization cannot achieve excellent properties such as high voltage resistance, high ionic conductivity, good mechanical properties, and dense interface layer. Therefore, the research and development of polymer electrolytes with high energy density, high specific energy, high mechanical strength, and high interface stability has become a major challenge.
[0004] For a long time in the past, people have proposed various strategies to face the above challenges, among which the introduction of fluorine is an effective one among many strategies. Due to the hydrophobicity, high and stable bond strength, special dielectric properties, strong electronegativity and polarity of fluorine, and the fact that fluorinated materials help to form a protective layer rich in inorganic components at the metal-electrolyte interface to prevent further chemical decomposition and destruction of the electrolyte, fluorine substances are widely used in various battery components to improve battery stability and other related performance. However, the addition of fluorine will trigger corresponding side effect mechanisms. For example, existing studies have found that solvents with a low degree of fluorination have relatively strong solubility but poor oxidative stability, while an increase in the degree of fluorination will improve oxidative stability at the expense of solubility. Therefore, semi-solid polymer electrolytes containing fluorine in both monomers and solvents have been studied. Although they can improve their antioxidant properties, the decrease in the solvent's solubility seriously affects the ion transport of the electrolyte, resulting in existing in-situ cured semi-solid polymer electrolytes that are not resistant to high voltage and have poor cyclic stability, which need to be solved urgently. Summary of the invention
[0005] The first aspect of the present invention aims to solve the problem mentioned in the background technology that the existing in-situ cured polymer electrolytes are not resistant to high voltage and have poor cycle stability, and proposes a preparation method for generalized fluorine-regulated high-performance battery materials, which can effectively improve the high-voltage resistance and stability of battery materials.
[0006] A method for preparing a generalized fluorine-regulated high-performance battery material comprises the following steps:
[0007] Step 1, preparing a fluorine-containing monomer;
[0008] Step 2, mixing 90 to 100 parts by mass of lithium salt and 450 to 500 parts by mass of ethylene carbonate, stirring and mixing evenly to obtain a mixed solution A, wherein the ethylene carbonate does not contain fluorine;
[0009] Step 3, mixing 80 to 95 parts by weight of the monomer with 11 to 16 parts by weight of the cross-linking agent, and mixing them evenly to obtain a mixed solution B;
[0010] Step 4, mixing the mixed solution A with 112.5 to 125 parts by weight of the mixed solution B, and then adding 0.1 to 0.18 parts by weight of an initiator thereto after the mixture is evenly mixed, stirring and mixing to obtain a pre-polymerization electrolyte;
[0011] Step 5, assembling the battery in sequence, and when the separator is assembled, dripping the pre-polymerization electrolyte on at least one side of the separator, and continuing to assemble after the dripping is completed until the assembly is completed;
[0012] Step 6, bake the assembled battery, and completely polymerize the electrolyte by heating; then take out the battery, cool it at room temperature, and obtain the lithium metal battery material. The present invention adopts the strategy of monomer containing fluorine and solvent not containing fluorine to prepare lithium metal battery materials. The introduction of fluorine element broadens the electrochemical window of the electrolyte and solves the problems of high pressure resistance commonly existing in existing research, and regulates the solvent not containing fluorine, solves the problem of low ionic conductivity of polymer electrolyte, and can effectively improve the high voltage resistance and stability of battery materials. In addition, by controlling the ratio of lithium salt, ethylene carbonate, monomer, cross-linking agent and initiator, and strictly controlling the order of mixing, combined with the strategy of monomer containing fluorine and solvent not containing fluorine to prepare lithium metal battery materials, a synergistic enhancement technical effect can be achieved, thereby further improving the high voltage resistance and stability of battery materials.
[0013] Preferably, the monomer is a combination of one or more of 2,2,2-trifluoroethyl acrylate, hexafluorobutyl acrylate, fluoroalkyl acrylate, hexafluoroisopropyl methacrylate, perfluoroalkylethyl acrylate, 1,1,1-trifluoro-2-trifluoromethyl-2-hydroxy-4-pentyl methacrylate, 2-methyl-2-(trifluoromethylsulfonamide)propyl methacrylate, 2,2,3,3-tetrafluoropropyl acrylate, and trifluoroethyl methacrylate. All of them are fluorine-rich monomers, which are conducive to achieving better effects.
[0014] Preferably, the lithium salt is a combination of one or more of lithium hexafluorophosphate, lithium bis(trifluoromethylsulfonyl)imide, lithium perchlorate, lithium bis(fluorosulfonyl)imide, lithium bis(oxalatoborate), lithium difluorooxalatoborate, and lithium tetrafluoroborate.
[0015] Preferably, the crosslinking agent is an acrylic acid or methacrylic acid crosslinking agent.
[0016] Preferably, the initiator is a combination of one or more of azobisisobutyronitrile, azobisisovaleronitrile, azobisisoheptanenitrile, benzoyl peroxide, and lithium iodide.
[0017] Preferably, the diaphragm is one of an electrospun polyimide membrane, a glass fiber membrane, a polyethylene diaphragm, a polypropylene diaphragm, and an electrospun polyvinylidene fluoride membrane.
[0018] The second aspect of the present invention is to solve the problem of further improving the high-voltage resistance and stability of battery materials. Further, the volume proportion of the mixed solution A in the electrolyte before polymerization is 75% to 85%. The previous experiments showed that the high-voltage resistance and stability of battery materials can be further improved by configuring the volume proportion of the mixed solution A in the electrolyte before polymerization to 75% to 85%.
[0019] Preferably, the mass ratio of the mixed solution A to the mixed solution B is 1:4. This can further improve the high voltage resistance and stability of the battery material.
[0020] Preferably, the stirring time in step 2 is 30 to 60 minutes, which is conducive to more uniform mixing of the lithium salt and the ethylene carbonate.
[0021] Preferably, the stirring time in step 4 is 20 to 30 minutes, which is conducive to more complete and uniform mixing of the initiator with the mixed solution A and the mixed solution B.
[0022] Preferably, in step 5, the pre-polymerization electrolyte is dripped on both sides of the separator, which is more conducive to forming a protective layer rich in inorganic components at the metal-electrolyte interface, which can better prevent further chemical decomposition and damage of the electrolyte, and can effectively improve the high-voltage resistance and stability of the battery material.
[0023] Preferably, in step 5, the amount of the pre-polymerization electrolyte added is 40-50 μL. Ensuring that the pre-polymerization electrolyte fully infiltrates the diaphragm is beneficial to further improve the high-voltage resistance and stability of the battery material.
[0024] Preferably, in step 5, the operation is carried out in a glove box, and the positive electrode shell, the positive electrode sheet, the diaphragm, the lithium metal sheet, the gasket, the spring sheet, and the negative electrode shell are assembled in this order.
[0025] Preferably, the active material of the positive electrode plate is high-voltage lithium cobalt oxide or nickel-cobalt-manganese ternary positive electrode.
[0026] Optionally, in step 6, the baking temperature is 50-80° C. This is more conducive to complete polymerization of the electrolyte, thereby effectively improving the high-voltage resistance and stability of the battery material.
[0027] Preferably, in step 6, the baking temperature is 70°C.
[0028] Preferably, in step 6, the cooling time at room temperature is 12 to 30 hours.
[0029] Preferably, in step 6, the cooling time at room temperature is 24 hours.
[0030] Preferably, in step 6, the assembled battery is baked in an oven.
[0031] Compared with the prior art, the present invention provides a method for preparing a generalized fluorine-regulated high-performance battery material, which adopts a fluorine-containing monomer and a fluorine-free solvent strategy to prepare lithium metal battery materials. The fluorine element is introduced to broaden the electrochemical window of the electrolyte and solve the problems of high-voltage resistance that are common in existing research, and the solvent is fluorine-free, which solves the problem of low ionic conductivity of the polymer electrolyte, and can effectively improve the high-voltage resistance and stability of the battery material. BRIEF DESCRIPTION OF THE DRAWINGS
[0032] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the drawings required for use in the embodiments are briefly introduced below. It should be understood that the following drawings only show certain embodiments of the present invention and therefore should not be regarded as limiting the scope. For ordinary technicians in this field, other related drawings can be obtained based on these drawings without creative work.
[0033] Figure 1 The present invention is a flow chart of a method for preparing high-performance battery materials regulated by generalized fluorine.
[0034] Figure 2 The AC impedance curves of the generalized fluorine-regulated high-performance battery materials obtained in Example 1 and Comparative Example 1, wherein the abscissa is the real part of the impedance Z and the ordinate is the imaginary part of the impedance Z.
[0035] Figure 3 The linear sweep voltammetry curves of the generalized fluorine-regulated high-performance battery materials obtained in Example 2 and Comparative Example 2.
[0036] Figure 4 These are the rate performance test results of the generalized fluorine-regulated high-performance battery materials obtained in Example 2.
[0037] Figure 5 The generalized fluorine-regulated high-performance battery material obtained in Example 2 has charge and discharge cycle performance at a high cut-off voltage of 4.4V and a rate of 0.5C. DETAILED DESCRIPTION
[0038] The technical solutions in the embodiments of the present invention will be clearly and completely described below in conjunction with the drawings in the embodiments of the present invention. Obviously, the described embodiments are only a part of the embodiments of the present invention, rather than all the embodiments. The components of the embodiments of the present invention generally described and shown in the drawings here can be arranged and designed in various different configurations. Therefore, the following detailed description of the embodiments of the present invention provided in the drawings is not intended to limit the scope of the claimed invention, but merely represents the selected embodiments of the present invention. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without making creative work belong to the scope of protection of the present invention.
[0039] A method for preparing a generalized fluorine-regulated high-performance battery material comprises the following steps:
[0040] Step 1, prepare a fluorine-rich monomer, remove water and impurities, and store it at low temperature for use. For example, during implementation, 10 to 15 mL of fluorine-rich monomer can be taken, and after removing water and impurities through a molecular sieve, it can be stored at 2 to 8 ° C for use. In this embodiment, the fluorine-rich monomer can be 2,2,2-trifluoroethyl acrylate, hexafluorobutyl acrylate, fluoroalkyl acrylate, hexafluoroisopropyl methacrylate, perfluoroalkylethyl acrylate, 1,1,1-trifluoro-2-trifluoromethyl-2-hydroxy-4-methylacrylate pentyl ester, 2-methyl-2-(trifluoromethylsulfonamide)propyl methacrylate, 2,2,3,3-tetrafluoropropyl acrylate, trifluoroethyl methacrylate, or a combination of several thereof.
[0041] Step 2, 90 to 100 parts by mass of lithium salt and 450 to 500 parts by mass of ethylene carbonate are mixed, stirred and mixed evenly to obtain a mixed solution A, and then the mixed solution A is sealed with a sealing glue, and stored at low temperature for standby use, for example, it can be stored for standby use at 2 to 8 ° C. In implementation, the stirring time can be preferably 30 to 60 minutes, which is conducive to a more uniform mixing of the lithium salt and ethylene carbonate. In this embodiment, ethylene carbonate is a solvent, and lithium salt is added to ethylene carbonate to form an electrolyte, that is, the mixed solution A is an electrolyte. In this embodiment, ethylene carbonate also does not contain fluorine. In implementation, the lithium salt can preferably use a fluorine-free lithium salt, for example, lithium perchlorate or lithium bis(oxalate)borate, etc., so as to further improve the high voltage resistance and stability of the battery material. However, since the content of lithium salt is very low, in implementation, the lithium salt can also be a combination of one or more of lithium hexafluorophosphate, lithium bis(trifluoromethylsulfonyl)imide, lithium bis(fluorosulfonyl)imide, lithium difluorooxalatoborate, and lithium tetrafluoroborate. At this time, according to previous experiments, a battery material with higher high-voltage resistance and greater stability can still be obtained.
[0042] Step 3: Take 80-95 parts by weight of the monomer dried in step 1 and mix them with 11-16 parts by weight of a cross-linking agent, and mix them evenly to obtain a mixed solution B. In the implementation, the cross-linking agent can preferably be an acrylic cross-linking agent or a methacrylic cross-linking agent.
[0043] Step 4: Mix the mixed solution A obtained in step 2 with 112.5 to 125 parts by mass of the mixed solution B. After mixing evenly, add 0.1 to 0.18 parts by mass of the initiator thereto, and mix by stirring. During implementation, the stirring time can be 20 to 30 minutes, which is conducive to a more complete and uniform mixing of the initiator with the mixed solution A and the mixed solution B, and finally obtain the pre-polymerization electrolyte. The pre-polymerization electrolyte can be stored at 2 to 8 ° C for subsequent assembly into a battery. In this embodiment, the mixed solution A and the mixed solution B are fully mixed before adding the initiator, which can effectively prevent the initiator from reacting with the mixed solution A or the mixed solution B alone in advance, which is conducive to obtaining a better quality pre-polymerization electrolyte.
[0044] During implementation, the initiator may preferably be a combination of one or more of azobisisobutyronitrile, azobisisovaleronitrile, azobisisoheptanenitrile, benzoyl peroxide, and lithium iodide.
[0045] Step 5, in a glove box, assemble the battery in sequence. The assembly of the battery requires the positive and negative electrode shells, gaskets, springs, positive electrode sheets, diaphragms and lithium metal sheets of the battery. During implementation, the cleaned and dried positive and negative electrode shells, gaskets, springs, positive electrode sheets, diaphragms and lithium metal sheets of the battery can be assembled in the order of positive electrode shell, positive electrode sheet, diaphragm, lithium metal sheet, gasket, springs and negative electrode shell; when the diaphragm is assembled, the pre-polymerization electrolyte is dripped on at least one side of the diaphragm, and the pre-polymerization electrolyte is infiltrated into the diaphragm. After the dripping is completed, the lithium metal sheet, gasket, springs, negative electrode shell, etc. are continued to be assembled in sequence until the assembly is completed.
[0046] In implementation, the separator can preferably be one of an electrospun polyimide membrane, a glass fiber membrane, a polyethylene separator, a polypropylene separator, and an electrospun polyvinylidene fluoride membrane, which is conducive to achieving a better wetting effect. In implementation, the active material of the positive electrode plate can be a high-voltage lithium cobalt oxide or a nickel-cobalt-manganese ternary positive electrode. In implementation, the pre-polymerization electrolyte can be dripped only on one side of the separator, or the pre-polymerization electrolyte can be dripped on both sides of the separator, which is conducive to achieving a better effect.
[0047] During implementation, the amount of pre-polymerization electrolyte added can be determined according to actual needs. Preferably, in this embodiment, the amount of pre-polymerization electrolyte added to one side of the diaphragm can be preferably 40 to 50 μL. For example, the amount of pre-polymerization electrolyte can be preferably 40 μL, 45 μL, 50 μL, etc.
[0048] Step 6: Bake the assembled battery so that the electrolyte is completely polymerized by heating; during implementation, the assembled battery can be placed in an oven for baking, and the baking temperature can be preferably 50-80°C, for example, 60°C, 65°C, 70°C, etc. After baking, take the battery out of the oven and let it stand at room temperature to cool. During implementation, the cooling time at room temperature can be preferably 12-30 hours, for example, 20 hours, 24 hours, etc., and the lithium metal battery material is obtained after cooling.
[0049] In this embodiment, in the obtained lithium metal battery material, the monomer can preferentially account for 16-18wt%, the cross-linking agent can preferentially account for 0.03-0.08wt%, the lithium salt can preferentially account for 0.12-0.34wt%, and the ethylene carbonate can preferentially account for 80-83wt%. In addition, during implementation, the volume proportion of the mixed solution A in the electrolyte before polymerization is 75%-85%. The previous experiments show that the volume proportion of the mixed solution A in the electrolyte before polymerization is configured to be 75%-85%, which can further improve the high-voltage resistance and stability of the battery material. During implementation, the volume proportion of the mixed solution A in the electrolyte before polymerization can preferentially be 78%, 80%, 82%, etc. In this embodiment, the mass ratio of the mixed solution A to the mixed solution B is 1:4, which can further improve the high-voltage resistance and stability of the battery material.
[0050] This preparation method uses a fluorine-rich monomer and a cross-linking agent combined with a solvent, ethylene carbonate, to generate a generalized semi-fluorinated polymer electrolyte in situ. Fluorination is a common way to improve the defects of lithium-ion batteries, and can effectively improve the mechanical properties and electrochemical properties of the battery, but excessive fluorination may cause related negative effects. The construction of the generalized semi-fluorinated electrolyte in the present invention can effectively alleviate the related negative effects of excessive fluorine, reduce ion transfer barriers, improve antioxidant capacity, and enhance intermolecular forces, thereby further improving the high-voltage resistance and ionic conductivity of the battery. The generalized semi-fluorinated electrolyte has excellent chemical stability and can inhibit the degradation of the electrolyte and the growth of lithium dendrites, thereby improving the cycle life of the battery, effectively solving a series of difficult problems existing in current materials, and can significantly improve the high-voltage resistance and stability of battery materials.
[0051] Example 1
[0052] This embodiment 1 provides a method for preparing a generalized fluorine-regulated high-performance battery material, comprising the following steps:
[0053] Step 1: Prepare the pre-polymerization electrolyte in a glove box filled with argon (O2<0.1ppm, H2O<0.1ppm), including:
[0054] 1.1 Add 86.2 parts by mass of lithium bis(trifluoromethylsulfonyl)imide to 438 parts by mass of ethylene carbonate, stir for 45 minutes to mix evenly, and obtain a mixed solution A; then seal the mixed solution A with a sealing glue and store it at 2-8°C for later use.
[0055] 1.2 Take 85 parts by mass of 2,2,2-trifluoroethyl acrylate from which water and impurities have been removed in advance and mix with 15.3 parts by mass of polyethylene glycol diacrylate, and stir evenly to obtain a mixed solution B.
[0056] 1.3 Take 400 parts by mass of the mixed solution A and 100 parts by mass of the mixed solution B, mix them evenly, then add 0.12 parts by mass of azobisisobutyronitrile and mix them evenly to obtain a pre-polymerization electrolyte.
[0057] Step 2: Assembling battery materials (solid-state battery materials) in a glove box filled with argon (O2<0.1ppm, H2O<0.1ppm), including:
[0058] 2.1 Put the positive electrode shell, electrospun polyimide membrane, lithium metal sheet, gasket, shrapnel, negative electrode shell, etc. that have been cleaned and dried in advance into the glove box, and cut the high-voltage lithium cobalt oxide positive electrode sheet in advance, dry it and put it into the glove box for use;
[0059] 2.2 Assemble in the order of battery assembly. When the diaphragm is assembled, drip 40-50 μL of the pre-polymerized electrolyte obtained in step 1 on both sides of the diaphragm, press and seal, and then continue to assemble until the assembly is completed. In this embodiment, the positive electrode shell, high-voltage lithium cobalt oxide pole piece, electrospun polyimide membrane, lithium metal sheet, gasket, spring, and negative electrode shell are assembled in this order.
[0060] Step 3: Place the assembled battery in an oven and heat at 70°C for 3 hours to ensure that the electrolyte is completely polymerized. Then take out the battery and place it at room temperature for 24 hours to obtain the lithium metal battery material for testing.
[0061] Finally, the lithium metal battery obtained in this example was tested on a LAND charge and discharge instrument, first activated at 0.1C for 3 cycles, then long cycled at 0.5C. The data showed that during this process, the average coulomb efficiency was 99.9% and the cycle life was 248 cycles.
[0062] Example 2
[0063] Step 1: Prepare the pre-polymerization electrolyte in a glove box filled with argon (O2<0.1ppm, H2O<0.1ppm), specifically comprising:
[0064] 1.1 Add 81.15 parts by mass of lithium bis(trifluoromethylsulfonyl)imide to 435 parts by mass of ethylene carbonate, stir for 45 minutes to mix evenly, and obtain a mixed solution A. Then seal the mixed solution A with a sealing glue and store it at 2-8°C for later use.
[0065] 1.2 Take 85.71 parts by weight of hexafluorobutyl acrylate from which water and impurities have been removed in advance and mix with 14.29 parts by weight of polyethylene glycol diacrylate, and stir evenly to obtain a mixed solution B;
[0066] 1.3 Take 400 parts by mass of the mixed solution A and 100 parts by mass of the mixed solution B, mix them evenly, then add 0.12 parts by mass of azobisisobutyronitrile and mix them evenly to obtain a pre-polymerization electrolyte.
[0067] Step 2: Assembling battery materials in a glove box filled with argon (O2<0.1ppm, H2O<0.1ppm), including:
[0068] 2.1 Put the positive electrode shell, electrospun polyimide membrane, lithium metal sheet, gasket, shrapnel, negative electrode shell, etc. that have been cleaned and dried in advance into the glove box, and cut the high-voltage lithium cobalt oxide positive electrode sheet in advance, dry it and put it into the glove box for use.
[0069] 2.2 Assemble in the order of battery assembly. When the diaphragm is assembled, drip 40-50 μL of the pre-polymerized electrolyte obtained in step 1 on both sides of the diaphragm, press and seal, and then continue to assemble until the assembly is completed. In this embodiment, the positive electrode shell, high-voltage lithium cobalt oxide pole piece, electrospun polyimide membrane, lithium metal sheet, gasket, spring, and negative electrode shell are assembled in this order.
[0070] Step 3: Place the assembled battery in an oven and heat at 70°C for 3 hours to ensure that the electrolyte is completely polymerized. Then take out the battery and place it at room temperature for 24 hours to obtain the lithium metal battery material for testing.
[0071] Finally, the lithium metal battery obtained in this example was tested on a LAND charge and discharge instrument, first activated at 0.1C for 3 cycles and then long cycled at 0.5C. The data showed that during this process, the average coulomb efficiency was 99.81% and the cycle life was 360 cycles.
[0072] Example 3
[0073] Step 1: Prepare the pre-polymerization electrolyte in a glove box filled with argon (O2<0.1ppm, H2O<0.1ppm), specifically comprising:
[0074] 1.1 Add 86.3 parts by mass of lithium bis(trifluoromethylsulfonyl)imide to 440 parts by mass of ethylene carbonate, stir for 45 minutes to mix evenly, and obtain a mixed solution A. Then seal the mixed solution A with a sealing glue and store it at 2-8°C for use.
[0075] 1.2 Take 85 parts by weight of hexafluoroisopropyl methacrylate from which water and impurities have been removed in advance and mix with 14 parts by weight of polyethylene glycol diacrylate, and stir evenly to obtain a mixed solution B;
[0076] 1.3 Take 400 parts by mass of the mixed solution A and 100 parts by mass of the mixed solution B, mix them evenly, then add 0.12 parts by mass of azobisisobutyronitrile and mix them evenly to obtain a pre-polymerization electrolyte.
[0077] Step 2: Assembling battery materials in a glove box filled with argon (O2<0.1ppm, H2O<0.1ppm), including:
[0078] 2.1 Put the positive electrode shell, electrospun polyimide membrane, lithium metal sheet, gasket, shrapnel, negative electrode shell, etc. that have been cleaned and dried in advance into the glove box, and cut the high-voltage lithium cobalt oxide positive electrode sheet in advance, dry it and put it into the glove box for use;
[0079] 2.2 Assemble in the order of battery assembly. When the diaphragm is assembled, drip 40-50 μL of the pre-polymerized electrolyte obtained in step 1 on both sides of the diaphragm, press and seal, and then continue to assemble until the assembly is completed. In this embodiment, the positive electrode shell, high-voltage lithium cobalt oxide pole piece, electrospun polyimide membrane, lithium metal sheet, gasket, spring, and negative electrode shell are assembled in this order.
[0080] Step 3: Place the assembled battery in an oven and heat at 70°C for 3 hours to ensure that the electrolyte is completely polymerized. Then take out the battery and place it at room temperature for 24 hours to obtain the lithium metal battery material for testing.
[0081] Finally, the lithium metal battery obtained in this example was tested on a LAND charge and discharge instrument, first activated at 0.1C for 3 cycles and then long cycled at 0.5C. The data showed that during this process, the average coulomb efficiency was 99.92% and the cycle life was 262 cycles.
[0082] Example 4
[0083] Step 1: Prepare the pre-polymerization electrolyte in a glove box filled with argon (O2<0.1ppm, H2O<0.1ppm), including:
[0084] 1.1 Add 86.15 parts by mass of lithium bis(trifluoromethylsulfonyl)imide to 435 parts by mass of ethylene carbonate, stir for 45 minutes to mix evenly, to obtain a mixed solution A, then seal the mixed solution A with a sealing glue and store it at 2-8°C for later use;
[0085] 1.2 Take 85.5 parts by weight of perfluoroalkylethyl acrylate from which water and impurities have been removed in advance and mix with 14.1 parts by weight of polyethylene glycol diacrylate, and stir evenly to obtain a mixed solution B;
[0086] 1.3 Take 400 parts by mass of the mixed solution A and 100 parts by mass of the mixed solution B, mix them evenly, then add 0.12 parts by mass of azobisisobutyronitrile and mix them evenly to obtain a pre-polymerization electrolyte.
[0087] Step 2: Assembling battery materials in a glove box filled with argon (O2<0.1ppm, H2O<0.1ppm), including:
[0088] 2.1 Put the positive electrode shell, electrospun polyimide membrane, lithium metal sheet, gasket, shrapnel, negative electrode shell, etc. that have been cleaned and dried in advance into the glove box, and cut the high-voltage lithium cobalt oxide positive electrode sheet in advance, dry it and put it into the glove box for use;
[0089] 2.2 Assemble in the order of battery assembly. When the diaphragm is assembled, drip 40-50 μL of the pre-polymerized electrolyte obtained in step 1 on both sides of the diaphragm, press and seal, and then continue to assemble until the assembly is completed. In this embodiment, the positive electrode shell, high-voltage lithium cobalt oxide pole piece, electrospun polyimide membrane, lithium metal sheet, gasket, spring, and negative electrode shell are assembled in this order.
[0090] Step 3: Place the assembled battery in an oven and heat at 70°C for 3 hours to ensure that the electrolyte is completely polymerized. Then take out the battery and place it at room temperature for 24 hours to obtain the lithium metal battery material for testing.
[0091] Finally, the lithium metal battery obtained in Example 4 was tested on a LAND charge and discharge instrument, first activated at 0.1C for 3 cycles and then long cycled at 0.5C. The data showed that during this process, the average coulomb efficiency was 99% and the cycle life was 240 cycles.
[0092] Example 5
[0093] Step 1: Prepare the pre-polymerization electrolyte in a glove box filled with argon (O2<0.1ppm, H2O<0.1ppm), including:
[0094] 1.1 Add 86.3 parts by mass of lithium bis(trifluoromethylsulfonyl)imide to 435 parts by mass of ethylene carbonate, stir for 45 minutes to mix evenly, to obtain a mixed solution A, then seal the mixed solution A with a sealing glue and store it at 2-8°C for later use;
[0095] 1.2 Take 85.7 parts by weight of 2,2,3,3-tetrafluoropropyl acrylate from which water and impurities have been removed in advance and mix with 14.2 parts by weight of polyethylene glycol diacrylate, and stir evenly to obtain a mixed solution B;
[0096] 1.3 Take 400 parts by mass of the mixed solution A in step 1.1 and 100 parts by mass of the mixed solution B in step 1.2, mix them evenly, and then add 0.12 parts by mass of azobisisobutyronitrile to them and mix them evenly to obtain a pre-polymerization electrolyte.
[0097] Step 2: assembling high voltage battery materials in a glove box filled with argon (O2<0.1ppm, H2O<0.1ppm), including:
[0098] 2.1 Put the positive electrode shell, electrospun polyimide membrane, lithium metal sheet, gasket, shrapnel, negative electrode shell, etc. that have been cleaned and dried in advance into the glove box, and cut the high-voltage lithium cobalt oxide positive electrode sheet in advance, dry it and put it into the glove box for use;
[0099] 2.2 Assemble in the order of battery assembly. When the diaphragm is assembled, drip 40-50 μL of the pre-polymerized electrolyte obtained in step 1 on both sides of the diaphragm, press and seal, and then continue to assemble until the assembly is completed. In this embodiment, the positive electrode shell, high-voltage lithium cobalt oxide pole piece, electrospun polyimide membrane, lithium metal sheet, gasket, spring, and negative electrode shell are assembled in this order.
[0100] Step 3: Place the assembled battery in an oven and heat at 70°C for 3 hours to ensure that the electrolyte is completely polymerized. Then take out the battery and place it at room temperature for 24 hours to obtain the lithium metal battery material for testing.
[0101] Finally, the lithium metal battery obtained in Example 5 was tested on a LAND charge and discharge instrument, first activated at 0.1C for 3 cycles and then long cycled at 0.5C. The data showed that during this process, the average coulomb efficiency was 99.6% and the cycle life was 251 cycles.
[0102] Comparative Example 1
[0103] Comparative Example 1 is provided to illustrate that the preparation method provided by the present invention can improve the ionic conductivity of the battery.
[0104] The difference between Comparative Example 1 and Example 1 is that the fluorine-containing monomer in Example 1 is replaced by fluorine-free monomer butyl acrylate, and the remaining steps are the same as those in Example 1 to prepare a generalized fluorine-free lithium metal battery material.
[0105] The lithium metal battery material obtained in Comparative Example 1 was tested on a LAND charge and discharge instrument, first activated at 0.1C for 3 cycles, and then long cycled at 0.5C. The data showed that during this process, the average coulomb efficiency was 98.01% and the cycle life was 123 cycles.
[0106] Comparative Example 2
[0107] Comparative Example 2 is set up to prove that the preparation method provided by the present invention can effectively improve the electrochemical window, thereby effectively improving the high voltage resistance and cycle stability.
[0108] Comparative Example 2 is different from Example 2 in that: fluoroethylene carbonate is used as a fluorine-containing solvent, and the remaining steps are the same as those of Example 2 to obtain a generalized perfluorinated polymer lithium metal battery material in which both the monomer and the solvent contain fluorine.
[0109] The lithium metal battery material obtained in Comparative Example 2 was tested on a LAND charge-discharge instrument, first activated at 0.1C for 3 cycles, then long cycled at 0.5C, with an average coulombic efficiency of 98.7% and a cycle life of 180 cycles.
[0110] like Figure 1 As shown, Figure 1 is a schematic diagram of the AC impedance curve of the battery material obtained in Example 1 and Comparative Example 1, Figure 1 It can be seen that the ionic conductivity of the embodiment is doubled compared with that of the comparative example 1, indicating that the introduction of a certain amount of fluorine in the embodiment 1 can better form an ion fast transmission channel to conduct ions, thereby further improving the ionic conductivity performance.
[0111] like Figure 2 As shown, Figure 2 The linear sweep voltammetric curves of the high voltage battery materials obtained in Example 2 and Comparative Example 2 are shown in FIG. Figure 2 It can be seen that the electrochemical window in Example 2 is significantly widened, indicating that the semi-fluorinated polymer electrolyte effectively suppresses the negative effects of the perfluorinated polymer electrolyte and improves the high voltage resistance.
[0112] like Figure 3 As shown, Figure 3 The rate performance test results of the high voltage battery material obtained in Example 2 are as follows: Figure 3 It can be seen that Example 2 has a very excellent rate performance, and the rate can reach 6C while still maintaining a relatively high capacity.
[0113] like Figure 4 As shown, Figure 4The charge-discharge cycle performance of the high-voltage battery material obtained in Example 2 at a rate of 0.5C is shown in FIG. Figure 4 It can be seen that this embodiment has excellent high-pressure cycle stability.
[0114] The above description is only a specific implementation mode of the present invention, but the protection scope of the present invention is not limited thereto. Any technician familiar with the technical field can easily think of changes or substitutions within the technical scope disclosed by the present invention, which should be covered by the protection scope of the present invention.
Claims
1. A method for preparing a generalized fluorine-regulated high-performance battery material, characterized in that: The following steps are involved: Step 1, preparing a fluorine-containing monomer; Step 2, mixing 90 to 100 parts by mass of lithium salt and 450 to 500 parts by mass of ethylene carbonate, stirring and mixing evenly to obtain a mixed solution A, wherein the ethylene carbonate does not contain fluorine; Step 3, taking 80 to 95 parts by weight of the monomer and 11 to 16 parts by weight of the cross-linking agent and mixing them evenly to obtain a mixed solution B; Step 4, mixing the mixed solution A with 112.5 to 125 parts by weight of the mixed solution B, and then adding 0.1 to 0.18 parts by weight of an initiator thereto after the mixture is evenly mixed, stirring and mixing to obtain a pre-polymerization electrolyte; Step 5, assembling the battery in sequence, and when the separator is assembled, dripping the pre-polymerization electrolyte on at least one side of the separator, and continuing to assemble after the dripping is completed until the assembly is completed; Step 6: Bake the assembled battery to completely polymerize the electrolyte by heating; then take out the battery, cool it, and obtain the lithium metal battery material.
2. The method for preparing generalized fluorine-regulated high-performance battery materials according to claim 1, characterized in that: The volume proportion of the mixed solution A in the electrolyte before polymerization is 75% to 85%.
3. The method for preparing generalized fluorine-regulated high-performance battery materials according to claim 1, characterized in that: In the step 5, the pre-polymerization electrolyte is dripped onto both sides of the separator respectively.
4. The method for preparing generalized fluorine-regulated high-performance battery materials according to claim 1, characterized in that: In the step 5, the amount of the pre-polymerization electrolyte added is 40 to 50 μL.
5. The method for preparing generalized fluorine-regulated high-performance battery materials according to claim 1, characterized in that: In step 6, the baking temperature is 50-80°C.
6. The method for preparing generalized fluorine-regulated high-performance battery materials according to claim 1, characterized in that: The stirring time in step 2 is 30 to 60 minutes; the stirring time in step 4 is 20 to 30 minutes.
7. The method for preparing generalized fluorine-regulated high-performance battery materials according to claim 1, characterized in that: The monomer is a combination of one or more of 2,2,2-trifluoroethyl acrylate, hexafluorobutyl acrylate, fluoroalkyl acrylate, hexafluoroisopropyl methacrylate, perfluoroalkylethyl acrylate, 1,1,1-trifluoro-2-trifluoromethyl-2-hydroxy-4-pentyl methacrylate, 2-methyl-2-(trifluoromethylsulfonamide)propyl methacrylate, 2,2,3,3-tetrafluoropropyl acrylate, and trifluoroethyl methacrylate.
8. The method for preparing generalized fluorine-regulated high-performance battery materials according to claim 1, characterized in that: The diaphragm is one of an electrospun polyimide membrane, a glass fiber membrane, a polyethylene diaphragm, a polypropylene diaphragm, and an electrospun polyvinylidene fluoride membrane.
9. The method for preparing generalized fluorine-regulated high-performance battery materials according to claim 1, characterized in that: The lithium salt is a combination of one or more of lithium hexafluorophosphate, lithium bis(trifluoromethylsulfonyl)imide, lithium perchlorate, lithium bis(fluorosulfonyl)imide, lithium bis(oxalatoborate), lithium difluorooxalatoborate, and lithium tetrafluoroborate.
10. The method for preparing generalized fluorine-regulated high-performance battery materials according to claim 1, characterized in that: The cross-linking agent is an acrylic acid or methacrylic acid cross-linking agent; The initiator is a combination of one or more of azobisisobutyronitrile, azobisisovaleronitrile, azobisisoheptanenitrile, benzoyl peroxide, and lithium iodide.